FATWA DAR AL-IFTA NOMOR 3598/2006 TENTANG WAKAF SAHAM: TINJAUAN ARGUMENTASI HUKUM DAN IMPLIKASINYA - Arzam, Arzam; Fauzi, Muhammad; Akana Helmi, Lika; Mahdi, Al- (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2024)
Whether we realize it or not, there is a role and results of the inspiration of fatwas of scholars (personally or collectively) in addition to laws and regulations in various Islamic countries on innovation and development of waqf objects. Dar al-Ifta Egypt is one of them, has issued many fatwas on innovation of waqf objects, including on stock waqf and distribution of benefits, which is contained in fatwa no. 3598 of 2006 on Waqf al-Ashumi wa Tasbil 'Awa'idiha. This study aims to determine the legal status and arguments in the fatwa of Dar al-Ifta. This study is a qualitative study, with research data sourced from primary data in the form of the fatwa, using content analysis as a data analysis tool. This study shows that Dar al-Ifta has determined in its fatwa that stock waqf and distribution of benefits are permissible. Dar al-Ifta's argument for allowing it is using the concept of analogy (equation) regarding the permissibility of cash waqf. Dar al-Ifta strengthens its fatwa argument by referring to several arguments, where the arguments are the opinions of the scholars of the School of Thought about the permissibility of cash waqf (dinar and dirham). By knowing the legal status and arguments of the Dar al-Ifta fatwa, shares are determined as something that has the same function and benefits as money so that it can be used as an object of waqf (such as in the category of movable objects). This fatwa has implications for efforts to reform Islamic law in the field of waqf, and also has practical implications for society and for the increasingly advanced development of Islamic economics and finance. Furthermore, it is an open area for further research, related to the impact on the spread and response of society after the fatwa is issued or determined. It is also interesting to study the practice of stock waqf in various Islamic countries that are currently taking place, by linking it to existing fatwas and connecting it from various perspectives.